Etika Profesi Hakim Konstitusi dalam Menjaga Independensi Kekuasaan Kehakiman - Fathan Hariz (Esensi Hukum, 2025)
This study examines the role of professional ethics of constitutional judges in maintaining judicial independence within Indonesia’s constitutional system. Judicial independence constitutes a fundamental principle in a constitutional state as mandated by the 1945 Constitution of the Republic of Indonesia. However, ethical violations involving constitutional judges, particularly following Constitutional Court Decision Number 90/PUU-XXI/2023, have raised public concerns regarding the integrity and legitimacy of the Constitutional Court. This study employs a normative juridical method using statutory, conceptual, and case approaches through the analysis of constitutional provisions, statutory regulations, legal doctrines, and relevant court decisions. The findings indicate that professional ethics function not only as moral guidelines, but also as constitutional instruments for safeguarding judicial independence, impartiality, integrity, and public accountability. Weak ethical supervision mechanisms, political influence, and conflicts of interest may undermine the legitimacy of judicial institutions. Therefore, strengthening ethical oversight systems, transparent judicial recruitment, institutional accountability, and integrity-based legal culture are necessary to reinforce the credibility and independence of judicial power in Indonesia’s democratic rule of law system.